Interaksi Warfarin dan Aspirin terhadap Risiko Perdarahan pada Pasien Penderita Penyakit Kardiovaskular - Firli Reisya Subekti; Zahra Nurhafidah; Jasmine Rahma Saputri; Adhwa'a Kaylla; Jahra Almas Shadrina; Puteri Rahma Maharani; Mukarromah Dita Putri; Hadi Sudarjat; Indah Laily Hilmi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Cardiovascular disease (CVD) remains a leading cause of global morbidity and mortality; therefore, antithrombotic therapy such as warfarin and aspirin plays a crucial role in preventing thromboembolic events. The combination of these two agents provides a synergistic effect in inhibiting thrombus formation but significantly increases the risk of bleeding. Objective: To evaluate the impact of concominant ose of warfarin and aspirin on bleeding risk and its clinical benefits in patients with CVD. Methods: A systematic literature search was conducted using Google Scholar and Pubmed, with eligible studies analyzed. Result: The concomitant use of warfarin and aspirin increases the incidence of major bleeding without providing additional benefits in preventing stroke or myocardial infarction. Moreover, poor anticoagulation control further exacerbates this risk. Conclusion: The combination of warfarin and aspirin should be reserved only for patients with strong clinical indications, while warfarin monotherapy is safer for those with stable conditions. These findings emphasize the importance of individualized therapy evaluation and optimal INR monitoring to balance therapeutic benefits and bleeding risks.